Histologically Confirmed Recellularization is a Key Factor that Affects Meniscal Healing in Immature and Mature Meniscal Tears - Yan, Wenqiang; Dai, Wenli; Cheng, Jin; Fan, Yifei; Zhao, Fengyuan; Li, Yuwan; Maimaitimin, Maihemuti; Cao, Chenxi; Shao, Zhenxing; Li, Qi; Liu, Zhenlong; Hu, Xiaoqing; et al. (Frontiers in Cell and Developmental Biology, 2021)
Healing outcomes of meniscal repair are better in younger than in older. However, exact mechanisms underlying superior healing potential in younger remain unclear from a histological perspective. This study included 24 immature rabbits and 24 mature rabbits. Tears were created in the anterior horn of medial meniscus of right knee in each rabbit. Animals were sacrificed at 1, 3, 6, and 12 weeks postoperatively. We performed macroscopic and histological evaluations of post-meniscal repair specimens. Cells were counted within a region of interest to confirm cellularization at tear site in immature menisci. The width of cell death zone was measured to determine the region of cell death in mature menisci. Apoptosis was evaluated by TUNEL assay. Vascularization was assessed by CD31 immunofluorescence. The glycosaminoglycans and the types 1 and 2 collagen content was evaluated by calculating average optical density of corresponding histological specimens. Cartilage degeneration was also evaluated. Healing outcomes following untreated meniscal tears were superior in immature group. Recellularization with meniscus-like cell morphology was observed at tear edge in immature menisci. Superior recellularization was observed at meniscal sites close to joint capsule than at sites distant from the capsule. Recellularization did not occur at tear site in mature group; however, we observed gradual enlargement of cell death zone. Apoptosis was presented at 1,3,6,12 weeks in immature and mature menisci after untreated meniscal tears. Vascularization was investigated along the tear edges in immature menisci. Glycosaminoglycans and type 2 collagen deposition were negatively affected in immature menisci. We observed glycosaminoglycan degradation in mature menisci and cartilage degeneration, specifically in immature cartilage of the femoral condyle. In conclusion, compared with mature rabbits, immature rabbits showed more robust healing response after untreated meniscal tears. Vascularization contributed to the recellularization after meniscal tears in immature menisci. Meniscal injury fundamentally alters extracellular matrix deposition.